Teacher Profesionalism in Improving Children’s Speech Ability Speech Delay - Arsita Sari, Galuh; Rohmah, Lailatu; Nadlifah, Nadlifah (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2019)
The purpose of this study is to describe the professionalism of teachers in improving children's speech delay in speech delay. This research was conducted at KB Ceria Timoho Yogyakarta. This research uses a descriptive qualitative approach. The results showed that the professionalism of teachers in dealing with child speech delay at KB Ceria Timoho Yogyakarta through training in early detection of child growth and development, improvement of facilities and infrastructure that support the development of children's language, care and additional facilities needed to support children's language development such as laptop games music, song beetles, tools for watching movies, story books, puppets for stories, presenting people from the education office for information about the curriculum and accreditation and enhancing learning programs by always innovating. The teacher's steps in improving children's speech ability